Reflection of coupled waves from the flat boundary surface of a nonlocal micropolar thermoelastic half-space containing voids. Issue 10 (3rd October 2021) - Kumar, Suraj; Tomar, S. K.
Abstract: Reflection behavior of a set of coupled longitudinal/transverse waves incident obliquely at the flat boundary surface of a nonlocal micropolar thermoelastic half-space containing voids is investigated. Appropriate boundary conditions are setup for mechanically stress-free and thermally insulated boundary surface of the half-space. The equations yielding the reflection coefficients and the expressions of corresponding energy ratios of various reflected waves are presented. The nature of dependence of the reflection coefficients and their corresponding energy ratios against the angle of incidence is studied numerically for a specific model. Effect of several parameters on the reflection coefficients as well as on the corresponding energy ratios is noticed and depicted graphically. It is found that the sum of the energy ratios is approximately equal to unity at each angle of incidence. Some earlier known results are also recovered as special cases of the present formulation.